2016
DOI: 10.1039/c6cp04925g
|View full text |Cite
|
Sign up to set email alerts
|

Conformational features of the Aβ42 peptide monomer and its interaction with the surrounding solvent

Abstract: Accumulation of the amyloid beta (Aβ) peptide in the brain is responsible for debilitating neurodegenerative diseases, such as Alzheimer's disease (AD). We have carried out atomistic molecular dynamics simulations of the full-length Aβ peptide monomer with a wide range of conformations at room temperature. Efforts have been made to probe the conformational features of different segments of the peptide, namely the two terminal segments (N-term and C-term), the central hydrophobic regions (hp1 and hp2) and the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 92 publications
6
41
0
Order By: Relevance
“…In this study, AMD, in agreement with experimental data, revealed strong structural propensity of four homologous sequences in repeat domains to form turns and highlighted the potential of this specific conformational transition as an inhibitory mechanism against pathological transformation. Our previous studies have implemented AMD to sample the conformational space of full-length A peptide, which has been further used to understand the correlations with the structure and dynamics of surrounding water molecules [69][70] . The probability of finding a molecular system in one state or another depends on the free-energy difference between two states.…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 99%
“…In this study, AMD, in agreement with experimental data, revealed strong structural propensity of four homologous sequences in repeat domains to form turns and highlighted the potential of this specific conformational transition as an inhibitory mechanism against pathological transformation. Our previous studies have implemented AMD to sample the conformational space of full-length A peptide, which has been further used to understand the correlations with the structure and dynamics of surrounding water molecules [69][70] . The probability of finding a molecular system in one state or another depends on the free-energy difference between two states.…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 99%
“…The amino acid residues of the Aβ 42 fibril peptide chain is given below (Scheme 1) (18), where the colors correlate to the hydropathy index (24): green = polar [(−3.2) − (−4.5)] and red = non-polar [(+4.5) - (+2.8)]. As can be seen, the Aβ 42 molecule's sequence includes a polar/non-polar proportion of 14/14, where the N-terminal half has 10 polar and the C-terminal has eight non-polar residues, i.e.…”
Section: The Aβ 42 Peptide Monomermentioning
confidence: 99%
“…Also the thermodynamic parameters of the Aβ 42 monomer fibril were calculated (18). Considering the calculated binding energies [(tagged potential energy (TPE) (U TPE )] of the hydration water according to the segments are as follows: As a reference, the average TPE of the pure bulk water is −19.7 kcal mol The extracellular Aβ 40 and Aβ 42 fibril peptides Petkova and coworkers (28) studied in detail the molecular structure of the Aβ 40 fibril protein using the solid NMR technique, and also using X-ray fiber diffraction, transmission electron microscopy and MD simulations.…”
Section: The Aβ 42 Peptide Monomermentioning
confidence: 99%
See 2 more Smart Citations